Olive leaves extract alleviates inflammation and modifies the intrinsic apoptotic signal in the leukemic bone marrow - Nath, Priyatosh; Modak, Snehashish; Aktar, Tamanna; Maiti, Sharanya; Ghosh, Anisha; Singh, Riddha; Debnath, Mousumi; Saha, Bhaskar; Maiti, Debasish (Frontiers in Immunology, 2023)
Current anti-leukemic chemotherapies with multiple targets suffer from side effects. The synthetic drugs with huge off-target effects are therefore detrimental to leukemic patients. Therefore, natural plant-based products are being increasingly tested for new anti-leukemic therapy with less or no side effects. Herein, we report the effect of ethanolic olive leaves extract (EOLE) on K562 cell line and on the bone marrow of N-N’ Ethylnitrosourea (ENU)-induced leukemic mice. Using standard methodologies, we assessed viability, chromatin condensation, and induction of apoptosis in EOLE-treated K562 cells in-vitro. The anti-leukemic activity of EOLE was assayed by measuring ROS, levels of various cytokines, expression of iNOS and COX-2 gene, and changes in the level of important apoptosis regulatory and cell signaling proteins in-vivo. EOLE effected significant K562 cell apoptosis, reduced the number of blast cells in ENU-induced leukemic mice, reduced ROS production and enhanced expression of NF-κB and ERK1/2 in bone marrow of leukemic mice. EOLE also alleviated the inflammation as evident from reduced expression of IL-6, IL-1β, TNF-α, iNOS and COX2. Finally, EOLE induced apoptosis of bone marrow cells in leukemic mice. These data suggest that EOLE reduces ENU-induced inflammation and induces apoptosis in leukemic cells.